Inter shear transfer of unbonded prestressing precast segmental bridge column dry joints. (1st January 2018) - Bu, Zhan-Yu; Wu, Wei-Ye
Highlights: Precast segmental column dry joints specimens were tested under direct shear loading. New shear capacity calculation formulas were suggested. Contribution of friction to shear capacity was studied. Abstract: The shear performance of precast segmental bridge column (PSBC) epoxy-free dry joints was investigated. Ten PSBC dry joint specimens were tested under monotonic direct shear loading. The design parameters include sectional shape, with or without shear keys, key number and geometry, and confining stress. The shear resistance-relative vertical displacement curves were recorded. The damage patterns and failure mechanism of tested specimens were analyzed. Shear strength formulas for prismatic, castellated, and flat dry joint were derived through data regression. The applicability of proposed formulas together with those from literature was investigated. Finally a finite element (FE) model was calibrated to study the friction contribution to shear capacity at various confining stresses.